A GUIDE TO ESTABLISHING MANAGEMENT INFORMATION SYSTEM IN TERTIARY INSTITUTIONS IN NIGERIA - Wokocha, C. M.; Adebayo, E. I. (European Scientific Journal, ESJ, 2012)
Information is data that have been put into a meaningful and useful context and communicated to a recipient who uses it to make decisions. Information involves the communication and reception of intelligence or knowledge. It appraises and notifies surprises and stimulates, reduces uncertainty, reveals additional alternatives or helps eliminate irrelevant or poor ones, and influences individuals and stimulates them to action. An element of data may constitute information in a specific context; for example, when you want to contact your friend, his or her telephone number is a piece of information; otherwise, it is just one element of data in the telephone directory. To gain some insight into meeting the information needs of a tertiary institution, some understanding of the environment and the decision-making processes is necessary. This paper will focus on standard in establishing Management information systems in tertiary institution, so that information can be extracted from the operations systems so that, management can provide a stimulus for decision-making or information for decision-making.